Investigation of liquefaction in layered sands by means of shaking table tests - Ozener, P. T.; Berilgen, M.; Ozaydin, K. (TAYLOR & FRANCIS LTD, 2006)
In this paper the results of shaking table model tests which were conducted to investigate the liquefaction mechanism in layered soils are presented. The layered sand columns were constructed with a 1 cm thick seam of silt within the sand deposit to separate the upper and lower sand layers. The results from the layered sand showed that a water film is developed underneath the less permeable silt layer consistent with the observations of other investigators. The experiments were carried out under different peak input accelerations, surcharge pressure and on sand columns of different relative densities. This paper presents the experimental observations about pore pressure development at different depths of the sand column, generation of a water film underneath the silt seam when it is present, and post liquefaction behavior including surface settlements.
Keywords: Engineering